Conjunctivitis due to COVID-19 - Marsekal K. Polii; Wenny P. Supit; Imelda H. M. Najoan (e-CliniC, 2022)
Abstract: COVID-19 is a respiratory infectious disease due to SARS-CoV-2 virus. This virus requires angiotensin-converting enzyme 2 (ACE2) receptor to invade cells. ACE2 receptors are also found in the conjunctiva, therefore, the surface tissue of the eye can be a potential target for COVID-19 transmission. The most common ocular manifestation of COVID-19 is conjunctivitis. This study aimed to evaluate whether there was a relationship between conjunctivitis and COVID-19 disease. This was a literature review study using four databases, namely Pubmed, Google Scholar, Science Direct and Clinical Key. The keywords were COVID-19 AND conjunctivitis. The results showed that conjunctivitis due to COVID-19 could be one or the only symptom. The age range of COVID-19 positive samples with conjunctivitis symptoms was dominated by middle-aged to elderly. More often the patients had moderate to asymptomatic degree of symptoms. Supportive therapies such as artificial tear drops and cold compresses greatly helped the healing process. In conclusion, the transmission of COVID-19 infection due to SARS-CoV-2 virus can spread through the conjunctiva. Conjunctivitis can be the only symptom that appears due to COVID-19 infection or as an early sign of infection.Keywords: conjunctivitis; COVID-19Â Â Abstrak: COVID-19 merupakan penyakit infeksi menular pernapasan yang diakibatkan oleh virus SARS-CoV-2. Virus ini membutuhkan reseptor angiotensin-converting enzyme 2 (ACE2) untuk menginvasi sel-sel. Reseptor ACE2 juga ditemukan pada konjungtiva sehingga jaringan permukaan mata dapat menjadi target potensial untuk penularan COVID-19. Manifestasi okular akibat COVID-19 yang sering ditemukan ialah konjungtivitis. Penelitian ini bertujuan untuk mengevaluasi apakah terdapat hubungan antara konjungtivitis dengan COVID-19. Jenis penelitian ialah suatu literature review. Pencarian data menggunakan empat database Pubmed, Google Scholar, Science Direct dan Clinical Key dengan kata kunci yaitu COVID-19 AND conjunctivitis. Hasil penelitian mendapatkan bahwa konjungtivitis akibat COVID-19 dapat menjadi salah satu maupun satu-satunya gejala. Rentang usia sampel positif COVID-19 dengan gejala konjungtivitis didominasi oleh middle-aged sampai lanjut usia dan lebih sering pasien derajat gejala asimt-omatik-sedang. Terapi suportif seperti pemberian tetes air mata buatan dan kompres dingin sangat membantu proses penyembuhan. Simpulan penelitian ini ialah penularan infeksi COVID-19 yang disebabkan oleh virus SARS-CoV-2 dapat menyebar melalui konjungtiva. Konjungtivitis dapat menjadi satu-satunya gejala yang muncul akibat infeksi COVID-19 maupun sebagai tanda awal infeksi.Kata kunci: konjungtivitis; COVID-19